2014
DOI: 10.14710/jtsiskom.2.4.2014.267-276
|View full text |Cite
|
Sign up to set email alerts
|

Perancangan Jaringan Sensor Nirkabel (JSN) untuk Memantau Suhu dan Kelembaban Menggunakan nRF24L01+

Abstract: The environmental condition in a large areas often requires the monitoring. For example, in the case of greenhouse were used to cultivation experiments, fertilization experiments, plant resistance experiments, tissue culture experiments, experimental planting of crops in the off-season, and it needs equipment to monitor and control the environmental conditions to suit the characteristics required environment. The extent of land that is must be monitored, making it needs distribute the monitor at some point so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
1
0
5
Order By: Relevance
“…Packet loss is very significant when the distance between master and slave exceeds 800 m. Several authors have reported lower transmission ranges with the same RF communication module (NRF24L01); for example, in Ref. [25], transmission distances of 50, 100, and 150 m were reported between master and slave in a tree-blocked open space, and based on the data losses, the prototype had a good performance at distances below 100 m. Other reports have indicated an effective transmission range of 100 m for the NRF2401+ device (Nordic Semiconductor, Trondheim, Norway) in an open area [26]. The large differences between the reported transmission ranges may be due to vegetation affecting the RF transmission module.…”
Section: Testing At Environmental Conditionsmentioning
confidence: 99%
“…Packet loss is very significant when the distance between master and slave exceeds 800 m. Several authors have reported lower transmission ranges with the same RF communication module (NRF24L01); for example, in Ref. [25], transmission distances of 50, 100, and 150 m were reported between master and slave in a tree-blocked open space, and based on the data losses, the prototype had a good performance at distances below 100 m. Other reports have indicated an effective transmission range of 100 m for the NRF2401+ device (Nordic Semiconductor, Trondheim, Norway) in an open area [26]. The large differences between the reported transmission ranges may be due to vegetation affecting the RF transmission module.…”
Section: Testing At Environmental Conditionsmentioning
confidence: 99%
“…NRF24L01+ memiliki solusi terkait daya berupa daya ultra rendah yang memungkinkan daya tahan baterai berbulan-bulan. Modul ini dapat digunakan untuk pembuatan perangkat tambahan komputer, piranti permainan, piranti fitnes dan olahraga, mainan anak-anak dan alat lainnya [8].…”
Section: Model Wireless Nrf24l01/transmiterunclassified
“…Rangkaian elektrik (skematik) model sistem terdiri dari tiga yaitu skematik perangkat sepeda motor, perangkat helm dan perangkat pelacak GPS. Komunikasi data antara perangkat sepeda motor dan perangkat helm dihubungkan melalui modul nRF24L01 dengan Arduino nano bertindak sebagai mikrokontroler [6]. Dalam perangkat sepeda motor terdapat relay sebagai output serta sensor infra merah dan sensor ultrasonik sebagai input sedangkan perangkat helm memiliki buzzer dan speaker sebagai output serta limit switch sebagai input seperti ditunjukkan oleh Gambar 2.…”
Section: Pembuatan Model Sistemunclassified